Effect of production system on milk production and food consumption in goats (2017)
ABSTRACT: Objective. Assessing the effect of productive system in production, composition of milk and feed consumption in goats s. Materials and methods. Three production systems were assessed in Antioquia Department, Colombia. Dry matter intake (DMI), dry matter digestibility (DMD), production and composition of milk were assessed during two periods for 71 goats, Saanen and Alpine breed type. Regarding the statistical analysis the individual effects of different variables were taken into account, such as production system, breed, period, and the interaction between them; using the use of PROC MIXED in the statistical software SAS.. Results. The production system named A1 (semi-stabling, grazing on grasslands with natural vegetation succession) presented the highest milk production perday in both periods, with an average of 1.2 L/day, as well as higher levels of fat, protein and non-fatmilk solids (53, 33 and 84 g/day), compared to production systems A2 and A3 (permanent housing).These A2 and A3 systems presented an average of 0.6 L/day and dry matter intake (DMI) did not presented significant difference, however in vitro digestibility did. Conclusions. High variability was found in the assessed systems regarding the dry matter intake, as well as the composition of feed offered. There was also a significant effect in the production system on the amount of milk produced by animal per day.